Evaluasi Aplikasi Silsilah Keluarga FamilySearch Dengan Pengujian Usability - Vallian Kautsar Fahdrerazi; Ismiarta Aknuranda; Hanifah Muslimah Az-Zahra (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
Maintaining lineage for Muslims is important to avoiding certain sins. Digital bloodline recording media will help Muslims in remembering their bloodlines. One application that is already available is familysearch.org, developed by the FamilySearch and FamilySearch Tree organizations for mobile applications. But it is unknown whether this application can meet the needs of Muslims or not. Because of that, an usability evaluation was conducted on the applications that were available to see whether the application was able to meet the needs of Muslims or not. Data was obtained by testing the scenario to find usability problems for 5 participants by performing 28 tasks. The findings are grouped by thematic methods and it is found that the application still lacks the features needed for nasab for Muslims, the lack of instructions for use, the use of foreign languages, features adding information lacking the default category, a display that is less user-friendly for ordinary users, and general use will difficult for ordinary users. Recommendations given based on the findings include: the addition of complete information for Muslims regarding the passage, the addition of clearer instructions, the use of Indonesian, simplifying the appearance, and the category of adding more varied information.